Alignment of the rearfoot and foot pressure patterns of individuals with medial tibial stress syndrome: A cross-sectional study. (July 2019) - Kinoshita, Kazuo; Okada, Kyoji; Saito, Isao; Saito, Akira; Takahashi, Yusuke; Kimoto, Minoru; Wakasa, Masahiko
Abstract: Objective: To compare the rearfoot alignment (leg-heel angle, LHA) during standing and walking, and foot pressure during walking between individuals with medial tibial stress syndrome (MTSS) and asymptomatic individuals participating in daily sports. Design: A cross-sectional study. Setting: Research laboratory. Participants: MTSS (18 legs) and control (15 legs) participants. Main outcome measures: The LHA in the frontal plane during walking and standing; partial foot pressures expressed as the percentage of body weight (%PFP); and transverse width of the center of pressure (COP) path expressed as the percentage of foot width (%Trans) on walking. Results: The LHA while walking was significantly higher in MTSS individuals, whereas the LHA while standing was not significantly different. The %PFPs of medial metatarsal areas were significantly higher in MTSS patients, whereas the %Trans was significantly lower. Conclusions: In individuals with MTSS, the LHA is similar to controls while standing but higher (more everted) while walking while there is higher pressure under the medial metatarsal areas and the COP is more medial. Rearfoot malalignment in individuals with mild to moderate MTSS can be detected on walking, even if the alignment on standing is normal. Highlights: The athletes with medial tibial stress syndrome (MTSS) showed the rear foot eversion on walking in the stance phase. The athletes with MTSS showed high foot pressure of the medial metatarsal areas and narrow figure of center of pressure path. Rear foot malalignment in individuals with MTSS can be detected on walking, even if the alignment on standing is normal.